Digital Fatigue, Burnout, and Career Setbacks in Banking - Hadjri, Muhammad Ichsan; Leovani, Ega; Murti, Krisna; Adam, Ryan; Anggraini, Bean Nur (Jurnal Manajemen, 2025)
This study examines the effects of digital fatigue, work-family conflict (WFC), and perceived role overload on career regression among banking employees, with burnout as a mediating factor. Using a cross-sectional design, data were collected from 384 banking employees in Palembang through structured questionnaires. The findings reveal that digital fatigue, WFC, and role overload significantly contribute to burnout, which mediates their impact on career regression. Grounded in the Job Demands-Resources (JD-R) Theory, the results demonstrate that excessive job demands heighten the risk of burnout when unbalanced by sufficient resources, ultimately hindering career development. The study underscores the importance of organisational efforts to minimise digital demands, promote work-life balance, and manage workloads to mitigate burnout. Limitations include reliance on self-reported data and a focus on the banking sector. Future research should explore broader populations and examine additional factors such as social support and coping strategies.